IMPLEMENTASI LITERASI DIGITAL DI SMARTPHONE DALAM PENINGKATAN MOTIVASI DAN AKTIVITAS BELAJAR SISWA - Muhammad Nur; Umar Umar; Abdul Salam (Program Studi Informatika Universitas Teknologi Sumbawa, 2022)
The governor has determined that regional libraries can be used as centers for digitalization programs for the community. The purpose of this study was to find out: Is there any influence between digital literacy on smartphones in increasing student motivation and learning activities and is there any influence between motivations in increasing student learning activities. This research is quantitative.The technique of sampling used purposive sampling with the Slovin formula. Methods of data collection using questionnaires and unstructured interviews, analysis of research data using multiple linear regressions, T-test, with SPSS version 26. The results showed: (1) t-count value < t table (0.980 < 1.6671 ), sig value 0.330 > 0.05, H0 is rejected, (2) t-count value > t-table value (5.964 > 1.6671) sig value 0.000 <0.005 and (3) (6.930 > 1.66571) and Sig arithmetic < Sig table (0.000 < 0.05) means that H1 is accepted, Y = 6.709 + 0.202 X1 +0.504 X2, and the results of the Determination Correlation Test (R2) or the Adjusted R Square value of 0.681 mean the independent variables are digital literacy on smartphones and student learning motivation has an influence of 68.10% on student learning activities, the remaining 31.90% is influenced by other factors.